"In sickness and in health" - how neutrophil extracellular trap (NET) works in infections, selected diseases and pregnancy - Paulina Niedźwiedzka-Rystwej; Weronika Repka; Beata Tokarz-Deptuła; Wiesław Deptuła (BMC, 2019)
Abstract The discovery of the NET network (neutrophil extracellular trap) has revolutionized the perception of defense mechanisms used by neutrophils in infections and non-infectious states, as this mechanism proves the complexity of the ways in which neutrophils can act in the organism. The paper describes the NET network and its participation in bacterial, viral, fungal and parasitic infections, both in a positive and a negative aspect. In addition, attention was paid to the participation of NETs in the course of autoimmune diseases, cancer, as well as its impact on pregnancy and fertility in mammals.